2003
DOI: 10.1016/s0378-1097(03)00432-4
|View full text |Cite
|
Sign up to set email alerts
|

Mannheimia haemolyticaleukotoxin-induced increase in leukotriene B4production by bovine neutrophils is mediated by a sustained and excessive increase in intracellular calcium concentration

Abstract: Isolated bovine neutrophils were used to study the relationship between the duration and magnitude of the Mannheimia haemolytica leukotoxin-induced increase in intracellular calcium concentration and leukotriene B 4 synthesis. In contrast to recombinant human C 5a , which caused a transient, small increase in intracellular calcium concentration and no effects on leukotriene B 4 synthesis, exposure of neutrophils to leukotoxin resulted in a rapid, sustained, large increase in intracellular calcium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…SOCE is considered a potential target for therapeutic interventions in inflammatory diseases [35], as PMN Ca 2ϩ influx is increased in some infectious diseases and inflammatory processes, i.e., bacterial pneumonia [35,36]. In other cellular responses, such as pH i changes, MAPK and PI-3K phosphorylation is activated simultaneously in neutrophils and contributes to the tissue injury [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…SOCE is considered a potential target for therapeutic interventions in inflammatory diseases [35], as PMN Ca 2ϩ influx is increased in some infectious diseases and inflammatory processes, i.e., bacterial pneumonia [35,36]. In other cellular responses, such as pH i changes, MAPK and PI-3K phosphorylation is activated simultaneously in neutrophils and contributes to the tissue injury [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…4B (Fig. 5) It has been reported that glial cells can release ATP in both Ca't-dependent (14) and Ca't-independent (58) manner, and that calcium has a pivotal role in the biosynthetic production of leukotrienes (16). To examine the potential role of intracellular Ca (Fig.…”
Section: Effect Of 2mesatp and Of Ltd4 On Abp And Cyslt Release In Prmentioning
confidence: 99%
“…The present study con¢rmed that, in addition to in£ux of extracellular Ca 2þ , release of stored intracellular Ca 2þ via both ryanodine-and IP 3 -sensitive Ca 2þ channels contributes to LKT-induced increase in [Ca 2þ ] i . Previous studies have demonstrated that this high and sustained [Ca 2þ ] i is necessary to stimulate production of LTB 4 [8], which is correlated with development of acute, exudative M. haemolytica infection [3]. .…”
Section: And Ryanodine Receptor-operated Channelsmentioning
confidence: 97%
“…Furthermore, this reliance on extracellular Ca 2þ has been correlated with increased [Ca 2þ ] i , suggesting that LKT induces an in£ux of Ca 2þ across the plasma membrane. However, comparison between the e¡ects of various neutrophil activators, including LKT, A23187, and recombinant human C 5a , on the rate and degree of increase in [Ca 2þ ] i has indicated that the response to LKT cannot be explained entirely by in£ux of extracellular Ca 2þ across the plasma membrane, down a concentration gradient, because the rate at which [Ca 2þ ] i increases is too rapid to be explained by the ¢rst-order kinetics characteristic of di¡usional processes [8]. The present study con¢rmed that, in addition to in£ux of extracellular Ca 2þ , release of stored intracellular Ca 2þ via both ryanodine-and IP 3 -sensitive Ca 2þ channels contributes to LKT-induced increase in [Ca 2þ ] i .…”
Section: And Ryanodine Receptor-operated Channelsmentioning
confidence: 99%
See 1 more Smart Citation